2021
DOI: 10.1177/1178221820976988
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Barriers in the Substance Use Disorder Continuum of Care With Peer Recovery Support

Abstract: Substance Use Disorder (SUD) has been recognized as a chronic, relapsing disorder. However, much of existing SUD care remains based in an acute care model that focuses on clinical stabilization and discharge, failing to address the longer-term needs of people in recovery from addiction. The high rates of client’s disengagement and attrition across the continuum of care highlight the need to identify and overcome the obstacles that people face at each stage of the treatment and recovery process. Peer recovery s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 96 publications
1
23
0
Order By: Relevance
“…The need for a continuum of care was mentioned by a large proportion of the survey respondents. For example, service provider responses highlighted what has already been noted about the inadequacies of the “acute care models” 23 (ie, reducing symptoms, clinical stabilization, and subsequent discharge). Several participants indicated the importance of developing a continuum of care with regards to the continuation of service provision and support after treatment in hospitals, acute detox, and/or withdrawal management services.…”
Section: Results From Open-ended Questionsmentioning
confidence: 99%
“…The need for a continuum of care was mentioned by a large proportion of the survey respondents. For example, service provider responses highlighted what has already been noted about the inadequacies of the “acute care models” 23 (ie, reducing symptoms, clinical stabilization, and subsequent discharge). Several participants indicated the importance of developing a continuum of care with regards to the continuation of service provision and support after treatment in hospitals, acute detox, and/or withdrawal management services.…”
Section: Results From Open-ended Questionsmentioning
confidence: 99%
“… 29 Since not all programing is reimbursable and not all insurance plans make treatment services affordable, peer recovery support can be a vital tool for those seeking or maintaining recovery. 30 , 31 Referrals to peer recovery support from drug courts or healthcare centers is 1 way to provide free recovery based services, when appropriate. Additional ways to ensure access to treatment are needed such as providing transportation or reducing the cost of treatment services.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have indicated value in peer services, [6][7][8][9][10][11][12][13][14][15][16][17][18] including positioning peers in the linkage facilitator or treatment navigation role, [19][20][21] little research has focused on peer navigation specific to SUD treatment for recently incarcerated women. Findings highlight the breadth of needs reported by women in the present sample prior to release, including transportation, employment, housing, mental or physical health, and complex interpersonal relationships, all of which have been highlighted in previous research on women's reentry 16 and may pose as major barriers to engagement with OUD treatment and sustaining recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Peer-based services have demonstrated promise in supporting positive health outcomes for individuals seeking recovery from substance misuse. [6][7][8] Broadly, "peers" are individuals with lived experience (e.g., incarceration, mental health issues, and/or substance misuse) working in trained/certified staff positions to address a variety of needs, including advocacy, communitybuilding, role-modeling, resource-gathering, or motivational support. 9 Through a combination of professional training and lived experience, peers can bridge communication gaps between clinicians and clients and speak with legitimacy grounded in either/both the service user or trained specialist role.…”
mentioning
confidence: 99%